Dielectric Response Analysis Characteristic of Service-Aged XLPE Cables - Patchara Thongkong; Wiboon Promphanich; Patt Udomluksananon; Siwakorn Jeenmuang; Theerayod Wiangtong; Norasage Pattanadech (My University, 2024)
The main insulation used in plastic underground cables is cross-linked polyethylene (XLPE). The XLPE underground cable which has been utilized in service for a long time, has experienced various stresses, or so-called TEAM stresses. Consequently, the XLPE insulation will be degraded over time and lead to insulation properties degradation. This paper represents the dielectric response analysis technique for characterizing the insulation condition of the service-aged XLPE medium voltage underground cable. The dielectric response analysis was performed on the 22 kV XLPE underground cables that have been in service for more than 10 years and were directly buried. The dielectric response analysis measurement consists of a combination of polarization and depolarization current (PDC) measurement in the time-domain and frequency-domain spectroscopy (FDS) measurement. After that, test results were analyzed to evaluate the insulation condition and compare it to the new 22 kV underground cable. The analyzed dielectric response analysis test results will be reported in this paper.
Keywords: High voltage insulation and dielectric phenomena; Dielectric materials and actuators; Material Properties and Processing